Enhancing student's computational thinking skills with student-generated questions strategy in a game-based learning platform - Cheng, Yu-Ping; Lai, Chin-Feng; Chen, Yun-Ting; Wang, Wei-Sheng; Huang, Yueh-Min; Wu, Ting-Ting (Computers and education, 2023)
Computational thinking (CT), a way to think about solving problems, is recognized as a basic skill for the 21st century. Although game-based learning (GBL) has been shown to improve student's CT skills, students may fail to self-evaluate or debate as they play games, thus failing to develop higher-order thinking. Also not widely explored is how teachers are to practice the CT core competencies during the learning process to cultivate students' problem-solving thinking. As the adoption of student-generated questions (SGQ) is an instructional strategy to promote higher-order thinking, we develop a GBL platform that uses this strategy to enhance students' CT skills, learning motivation, and learning confidence. For this purpose, fifty-three primary school students were recruited for this study, and data were collected during four classes of experimental CT activities. This study shows that the experimental group using the SGQ strategy with a GBL platform exhibited significantly higher CT skills than the control group. In addition, with respect to learning motivation and learning confidence it is found that the experimental group also outperformed the control group. This confirms that integrating the SGQ strategy and CT core competencies fosters higher-order cognitive thinking in students in problem-solving through gamification of the learning environment, resulting in higher motivation and confidence to complete experimental activities. •This study used student-generated questions (SGQ) in game-based learning platform.•This study integrated five core competencies of computational thinking into SGQ.•This result indicated that SGQ enhanced student's computational thinking skills.•It was studied that SGQ could improve student's learning motivation and confidence.•This study confirmed the contribution of SGQ to computational thinking skills.